The Role Of Educational Management In Managing Citizenship Learning In Technology Based Primary Schools In The Era New Normal - Bahdin Nur Tanjung (EDUTECH, 2021)
For the education sector, we must first prepare the existing prerequisites, including school preparation, teachers, students and parents. Therefore, the open sector plan will follow the government's agreement, and the department that will be opened must already have an agreement to deal with Covid and must be implemented in stages. If the school cannot meet the agreed standards and the location of the school is in an unsafe area, then the government will not gradually open the education office. In other words, the education office must be fully prepared in the process of implementing learning and fully prepared. studying time. This research method uses literature study to collect articles that are considered relevant in the data import process. These articles have been adapted into several important fields so that they can convey data as thoughts and ideas as a whole